2017
DOI: 10.1002/adem.201700409
|View full text |Cite
|
Sign up to set email alerts
|

Smart Energetics: Sensitization of the Aluminum‐Fluoropolymer Reactive System

Abstract: The development of smart energetics is at the forefront of the research community. The desire is to have energetics that could have ON/OFF capability, tunable performance, and/or targeted energy delivery. Therefore, efforts have been focused on designing systems that respond to stimuli in a controlled manner. In this paper, nanoscale aluminum (nAl)/fluoropolymer reactive systems are studied and the piezoelectric nature of the fluoropolymers is used as a means to sensitize the system. Using a capacitor type set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Nanocomposites incorporating Al NPs are among some of the most widely used solid-state fuels due to the natural abundance of aluminum and high exothermicity of oxidation reactions involving aluminum. In particular, the interaction of Al NPs with reactive fluoropolymer films has attracted significant interest as fluoropolymers may be cast onto a diverse set of substrates and are compatible with additive manufacturing [ 1 , 2 , 3 , 4 , 5 ]. The reaction properties and mechanisms of energetic fluoropolymer films have been widely studied by measuring the reaction temperature evolution to understand thermal characteristics and heating kinetics [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites incorporating Al NPs are among some of the most widely used solid-state fuels due to the natural abundance of aluminum and high exothermicity of oxidation reactions involving aluminum. In particular, the interaction of Al NPs with reactive fluoropolymer films has attracted significant interest as fluoropolymers may be cast onto a diverse set of substrates and are compatible with additive manufacturing [ 1 , 2 , 3 , 4 , 5 ]. The reaction properties and mechanisms of energetic fluoropolymer films have been widely studied by measuring the reaction temperature evolution to understand thermal characteristics and heating kinetics [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, tuning the impact sensitivity, burning rate and other combustion properties in fluoropolymer bound energetics by using piezoelectricity and flexoelectricity has yet to be fully studied. Initial research by Row and Groven 15 reported a significant change in the impact sensitivity when a DC voltage was applied to the PVDF/Al and THV/Al reactive systems indicating the electroactive nature 15 . However, the characterization of piezoelectric or flexoelectric coefficients and any influence on the burning rate, impact sensitivity and other combustion characteristics have not been detailed.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques to induce the β phase include spin‐coating, 1,6 electrospinning, 13 drawing a sample with initial α phase 12,13 from the melt, 13 hot‐pressing 14 and from the addition of negatively charged nano‐sized fillers 12,13 . There has been some research into other promising dielectric polymers that exhibit electroactive properties, such as the terpolymer tetrafluoroethylene‐hexafluoropropylene‐vinylidene fluoride (THV), which exhibits a spontaneous polarization peak 15 while being non‐centrosymmetric. THV also has a 9% higher fluorine content than PVDF, which can enhance combustion properties when combined with appropriate fuels (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a common way to solve the aforementioned problems is to coat Al powder with organic fluorides, such as perfluorotetradecanoic acid, polyvinylidene fluoride, and polytetrafluoroethylene. These organic fluorides have high chemical stability and enhance the thermal oxidation behavior of Al because of the decomposition of the Al 2 O 3 surface layer through the formation of the AlF 3 phase sublimated at elevated temperatures. However, organic coatings applied to the Al surface substantially reduce the energy density and adversely affect the combustion rates of the latter.…”
Section: Introductionmentioning
confidence: 99%